PENGARUH MODAL PSIKOLOGIKAL TERHADAP PERSEPSI IKLIM KESELAMATAN KERJA YANG DIMEDIASI OLEH KEPUASAN KERJA PADA TENAGA PERAWAT RSUD MEURAXA BANDA ACEH - Fanny Nafa Dita; Nashrillah Anis (Departemen Manajemen, 2020)
This study aims to measure the effect of effect the psychological capital on the perception of work safety climate which is mediated by job satisfaction in civil servant nurses at RSUD Meuraxa Banda Aceh. The sample used in this study were the civil servant nurses at RSUD Meuraxa Banda Aceh is totalling 205 respondents. Data collection equipment used in this study was a questionnaire. The sampling technique used is Proportionated Stratified Random Sampling. The method of analysis to determine the effect of all the variables involved is Hierarchical Linear Modelling (HLM).Based on the result of the HLM analysis indicated that psychological capital partially influences the perception of work safety climate, psychological capital partially influences the job satisfaction, the job satisfaction partially influences the perception of work safety, and the job satisfaction mediates the psychological capital to the perception of work safety climate.